The Portuguese Dilemma of Unstable Pensions - Friedrich L. Sell (Intereconomics, 2022)
Portugal's high public debt, its weak economic growth and its great attractiveness for foreign tourists are legend. Less well known is its unstable system of public pensions. This article addresses the underlying economic and political reasons, such as poor labour productivity, low real wages, insufficient immigration of trained people and the failure to find alternative ways of financing retirement. NextGenerationEU will effectively soften Portugal's macroeconomic budget constraints, but it carries the risk of further postponement of necessary policy changes and reforms.
Keywords: H55; O52; O47; 330